Proceedings of the 2019 International Conference on Organizational Innovation (ICOI 2019) 2019
DOI: 10.2991/icoi-19.2019.117
|View full text |Cite
|
Sign up to set email alerts
|

Distributive Justice, Job Satisfaction and Organizational Commitment as Antecedents of Employee Performance: A Study in Indonesia National Health Insurance Workers

Abstract: The study is aimed to investigate the effects of distributive justice, job satisfaction and organizational commitment toward employee performance. The data were drawn from 80 employees at Indonesia National Health Insurance (call as BPJS) workers. The data is gathered by conducting field survey. The analysis of data using a Smart Partial Least Square to answer the proposed hypotheses. The results of this study indicate that distributive justice positively significant influences on job satisfaction. The distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 3 publications
1
7
0
1
Order By: Relevance
“…Still, finding research results that focus on the part of IWB mediating intrinsic motivation's influence on job satisfaction is not easy. Some research that supports the argument includes the work of [28], [4] and [26]. The results of these studies indicate that innovative work behaviour has a significant positive effect as a mediator on the influence of intrinsic motivation on job satisfaction.…”
Section: Innovative Work Behaviour Mediates the Relationship Between ...mentioning
confidence: 86%
See 1 more Smart Citation
“…Still, finding research results that focus on the part of IWB mediating intrinsic motivation's influence on job satisfaction is not easy. Some research that supports the argument includes the work of [28], [4] and [26]. The results of these studies indicate that innovative work behaviour has a significant positive effect as a mediator on the influence of intrinsic motivation on job satisfaction.…”
Section: Innovative Work Behaviour Mediates the Relationship Between ...mentioning
confidence: 86%
“…The population is the group of people, events, or things of interest that the researcher wants to investigate [28]. The population number in this study was 117 employees who worked at the Bantul Regency Transportation Office.…”
Section: Population Sampling and Datamentioning
confidence: 99%
“…The results of research by (Rivai, H. A., Reza, D. Y., & Lukito, 2019) shows that distributive justice has no direct effect on performance. However, distributive justice affects job satisfaction, job satisfaction affects performance.…”
Section: F Job Satisfaction Mediates the Effect Of Distributive Justi...mentioning
confidence: 93%
“…Studies that have examined the effect of OJ on EP indicated a positive relationship between OJ and EP. For example, [52] suggested that one of the important antecedents of EP is OJ. In a similar approach, [53] found that OJ has a significant effect on job satisfaction and EP.…”
Section: Organizational Justice and Employee Performancementioning
confidence: 99%